2021
DOI: 10.14202/vetworld.2021.1185-1196
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition and health properties of Sembung plant (Blumea balsamifera): A review

Abstract: Indonesia's mindset has been focusing on the use of natural medicines, food, and healing practices widely recognized by the nation's culture. Traditional medicines and herbs used in traditional medicine can often lead to the discovery of drugs against certain diseases. The aim of this review was to study evidence-based data on the importance of Sembung plant, Blumea balsamifera, as a potential traditional medicine. The distribution, ethnopharmacology, secondary metabolites, and bioactivity against several dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 92 publications
1
11
0
Order By: Relevance
“…to treat cough and asthma by taking a few leaves, boiling them in the water, and drinking the water 2 times a day with added brown sugar. Our finding is in line with a study by Widhiantara and Jawi (2021), which found that B. balsamifera plants can be used to treat sinusitis, colic pain, coughs, kidney stones, flu, or diuretics. This plant contains several phytochemicals, both volatile (terpenoids, fatty acids, phenols, alcohols, aldehydes, ethers, ketones, pyridines, furans, and alkanes) and non-volatile (flavonoids, flavanones, and chalcones).…”
Section: Cough and Asthmasupporting
confidence: 92%
“…to treat cough and asthma by taking a few leaves, boiling them in the water, and drinking the water 2 times a day with added brown sugar. Our finding is in line with a study by Widhiantara and Jawi (2021), which found that B. balsamifera plants can be used to treat sinusitis, colic pain, coughs, kidney stones, flu, or diuretics. This plant contains several phytochemicals, both volatile (terpenoids, fatty acids, phenols, alcohols, aldehydes, ethers, ketones, pyridines, furans, and alkanes) and non-volatile (flavonoids, flavanones, and chalcones).…”
Section: Cough and Asthmasupporting
confidence: 92%
“…To calculate the average and standard deviation of the seaweed sample data replication using SPSS Version 23.0 software (IBM, USA) (Hussain et al, 2021). Graphs were processed using GraphPad software Version 8.0 (GraphPad, USA) (Widhiantara et al, 2021). Tabulation of EDI, THQ, TTHQ, and target cancer risk of As data using Ms. Software.…”
Section: Discussionmentioning
confidence: 99%
“…This work provides a significant overview of the challenges leading to the development of seaweed which will be further investigated as a pharmaceutical ingredient, especially as an herbal medicine in the future (Widhiantara and Jawi, 2021). However, because heavy metals act as limiting factors, besides having important functions in plant physiology, including seaweed as a source of micronutrients for growth, it becomes dangerous if the amount is above the tolerance threshold (Esposito et al, 2018;Lentini et al, 2018).…”
Section: Content Of Heavy Metals On Brown Seaweedmentioning
confidence: 99%
“…(Chinese name, Ainaxiang) is a very famous medicinal plant and functional tea in China and many countries of Asia, such as Malaysia, Philippines, Vietnam, and Thailand for the treatment of many diseases (Huang et al, 2022;Tan et al, 2020). Previous phytochemical investigations on this plant revealed the presence of flavonoids, monoterpenes, and sesquiterpenes (Tan & Yan, 2019;Tan et al, 2013;Widhiantara & Jawi, 2021). Ainaxiang tablets is made from the total flavonoids extracts of the leaves of B. balsamifera.…”
Section: Introductionmentioning
confidence: 99%